Psychological Typhoon Eye Effect During the COVID-19 Outbreak - Wang, Guixiang; Zhang, Yan; Xie, Simiao; Wang, Pu; Lei, Guanghui; Bian, Yueran; Huang, Fei; Zhang, Jingyuan; Cao, Xiaochen; Luo, Na; Luo, Mingyan; Xiao, Qiang (Frontiers in Public Health, 2020)
Background The COVID-19 outbreak in Wuhan, Hubei, has caused serious consequences and severely affected people's lives and mental health, thus, their psychological stress and behaviors should be noticed. Methods This study mainly adopts the self-designed questionnaires and SPSS to assess and analyze the psychological and behavioral responses in different regions during the COVID-19 epidemic and whether the "psychological typhoon eye" effects might be observed. The questionnaires included three measurements subscales—Risk Cognitive subscale (RCS), Stress Response subscale (SRS), and Behavioral Response subscale (BRS). This survey used an online questionnaire (www.wjx.cn) to investigate psychological and behavioral information from three areas—that was affected to different degrees by COVID-19. Exploratory factor analysis (EFA) and principal component analysis (PCA) were conducted to explore the factorial structure of the RCS, SRS and BRS, and confirmatory factor analysis (CFA) was conducted to explore the structural validity. A revised 18-item questionnaire was completed. We conducted ANOVA and LSD for the items in the three subscales for the three regions. Results The results confirmed the hypothesis of psychological "typhoon eye" effects in the earlier period of the COVID-19 Outbreak and indicated that there were significant differences in cognition and emotions among the residents of the three areas, and the psychological typhoon eye(PTE) effects were found. The PTE effects might be the fastest happened during the COVID-19 outbreak, simultaneously, residents showed the PTE effects in their cognition, emotions, the degree of their cognitive and emotional responses was increased over geographical distance, but didn't show in their behavioral responses. Conclusion These findings of psychological "typhoon eye" effects indicated the sustainable mental health care of cognition and emotions was more urgently needed during the COVID-19 outbreak, and the measures should be different in different areas. Strengthening emotional guidance, education about protection consciousness and effective responses were specially for residents of worst-hit areas, who might not be picking up the epidemic situation seriously. Eliminating unprovoked fear and building a sense of security, timely "disconnection" from negative information, guiding accurate cognition of stress and acceptance of self-response were especially for residents from cities outside the worst-hit areas, who showed the most negative psychological reactions.